Global Leadership Program: A Madrasah’s Transformative Learning Initiative in Enhancing Students’ 21st Century Skills - Yuni Yulianti (Journal of Islamic Education Research, 2023)
In the ever-evolving 21st century, MA Darul Fikri, an integrated Islamic boarding school located in Sidoarjo, East Java, attempts to provide its students with an outstanding transformative educational program, called Global Leadership Program (GLP). This program aims at enhancing its students’ global perspectives, instilling moral values, as well as developing their 21st century skills. Employing a survey, interview, and observation, this mixed-method study accentuates the GLP's pivotal role in nurturing the students' twenty-first-century skills, such as Learning and Innovation Skills, Digital Literacies, and Life Skills, which are fundamental for the students to possess. The survey of 76 participants revealed a robust endorsement of the Global Leadership Program, with 72.17% recognizing a significant boost in 21st-century skills, while only 5.13% expressed disagreement with its impact. Interview insights, gathered from interviewing randomly selected five student participants who have filled out the questionnaire, delved deeper into the nuanced development of 21st-century competencies, particularly creativity, collaboration, leadership, communication skills, critical thinking, digital literacy, and life skills. Observation further enriched the study, providing valuable context to the multifaceted positive impact of GLP. In conclusion, GLP emerges as a transformative educational initiative, positively impacting on a spectrum of essential skills crucial for the students' success in the 21st century, particularly in the context of Islamic education institutions that have been previously assumed as conservative.